Apprehension and Strategy Use in Writing Two Types of Genres in a College EFL Context - 한호 (영어어문교육, 2024)
This study explores the aspects that EFL students worry about most and the strategies they predominantly rely on when writing two distinct genres. It also examines whether their apprehension and strategies differ between the two genres. Regarding these issues, I conducted two questionnaire-based studies. A total of 28 students in an EFL writing course participated in composing two essays representing different writing genres: Expository Writing (EW) and Narrative Writing (NW). After completing each activity, they responded to survey questionnaires addressing their EFL writing apprehension as well as their use of writing strategies. In terms of writing apprehension, the results indicate that ‘Fear of Evaluation’ received the highest score among the three categories of apprehension for both EW and NW, with no statistically significant differences observed between the two genres except ‘Negative Perception of Writing’. For the use of strategies, ‘Evaluating Product’ was the most frequently utilized among the three metacognitive strategies, while ‘Comprehending Processes’ was the most employed of the two cognitive strategies. Furthermore, I found no statistically significant differences in strategy use between EW and NW. I contend that EFL teachers should focus on reducing students' fear of evaluation and incorporate strategy-based writing instruction to enhance student’s writing skills.
Keywords: writing apprehension/writing strategy/genre/EFL writing